2019
DOI: 10.1007/978-3-030-16151-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Instructional Alignment, Time, Instructional Quality, Teacher Quality, and Student Mathematics Achievement

Abstract: Opportunity to learn (measured by time spent on teaching mathematics and mathematics content coverage) potentially acts as a mediator of instructional quality and teacher characteristics. Previous research used a multilevel structural equation model (SEM) to explore the relationship of teacher instructional quality (identified using a latent variable) to student mean outcomes at grade four. Here, this model is extended by incorporating two instructional quality variables related to opportunity to learn: teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, in the school model, the effect of the teaching experience and education level on student achievement has disappeared Mohammadpour & Abdul Ghafar, 2014). In addition, the effects of teachers' major study area (Atar, 2014; and professional development hours were not found to have a substantial effect on students' science or mathematics achievement (Burroughs et al, 2019;Önal, 2015). Thus, when socioeconomic status was controlled, it was seen that the teacher qualifications examined in the study did not have a significant effect on students' science and mathematics achievement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the school model, the effect of the teaching experience and education level on student achievement has disappeared Mohammadpour & Abdul Ghafar, 2014). In addition, the effects of teachers' major study area (Atar, 2014; and professional development hours were not found to have a substantial effect on students' science or mathematics achievement (Burroughs et al, 2019;Önal, 2015). Thus, when socioeconomic status was controlled, it was seen that the teacher qualifications examined in the study did not have a significant effect on students' science and mathematics achievement.…”
Section: Discussionmentioning
confidence: 99%